IMPLEMENTASI METODE PARTMETHOD AND WHOLE METHOD DALAM PEMBELAJARAN PENDIDIKAN JASMANI UNTUK MENINGKATKAN KETERAMPILAN PASSING BAWAH BOLA VOLI KELAS - Hasan Sifuddin; Astrid Chandra Sari; Muhamad Fauzi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2017)
This study aims to determine the implementation of the method part and the whole method (part method and whole method) in Physical Education learning to improve the passing under volleyball of VIII grade MTs. Salafiyah Syafi’iyah Sukosewu Bojonegro. This research is a classroom action research with Kemmis and McTaggart's research design which consists of four stages, namely planning, action, observation, and reflection. The study was conducted by providing action in two cycles. The research subjects consisted of three 30 students of class VIII MTs. Salafiyah Syafi’iyah Sukosewu Bojonegro. Data collection techniques are carried out by means of observation and test the ability of the concept of motion. The method applied to VIII MTs. Salafiyah Syafi'iyah Sukosewu Bojonegro is by way of teachers and researchers demonstrating the movements of directly interacting in children with appropriate method steps such as: previews, analysis, experiments, training units, review, synthesis, and stabilization. The results showed that the application of the part method and the whole method (part method and whole method) could improve the passing ability of students of VIII MTs. Salafiyah Syafi’iyah Sukosewu Bojonegro. In addition there was an increase as evidenced by the percentage value on the passing ability test that met the minimum completeness criteria of 65%. One of the subjects obtained a percentage of achievement of 51% in the pre-action ability then increased to 60% in the post-test cycle I, and increased again to 72% in the post-test cycle II. In the pre-action ability of one of the other subjects gained a percentage of 43% achievement then increased to 55% in the post-test cycle I, and increased again to 66% in the post-test cycle II. Whereas one of the subjects obtained a percentage of achievement of 52% in pre-action ability, then increased to 58% in post-test cycle I, and increased again to 69% in post-test cycle II.